(untitled) (Avocetta, 2020)
Subsequent to the publication of the following paper in Avocetta, the authors were made aware of an error in the dataset affecting the results presented in Table 4. After re-analysing the data, the new dataset failed to uphold the original conclusions and the authors have requested a retraction of the original manuscript to sustain the integrity of their findings. Panter, C.T., Atkinson, E.D. & White, R.L. 2019. Quantifying the global legal trade in live CITES-listed raptors and owls for commercial purposes over a 40-year period. Avocetta 43(1): 23-36. Doi: https://doi.org/10.30456/ AVO.2019104